The Zinc-Finger Thylakoid-Membrane Protein FIP Is Involved With Abiotic Stress Response in Arabidopsis thaliana - Lopes, Karina L.; Rodrigues, Ricardo A. O.; Silva, Marcos C.; Braga, Wiliane G. S.; Silva-Filho, Marcio C. (Frontiers in Plant Science, 2018)
Many plant genes have their expression modulated by stress conditions. Here, we used Arabidopsis FtsH5 protease, which expression is regulated by light stress, as bait in a yeast two-hybrid screen to search for new proteins involved in the stress response. As a result, we found FIP (FtsH5 Interacting Protein), which possesses an amino proximal cleavable transit peptide, a hydrophobic membrane-anchoring region, and a carboxyl proximal C4-type zinc-finger domain. In vivo experiments using FIP fused to green fluorescent protein (GFP) showed a plastid localization. This finding was corroborated by chloroplast import assays that showed FIP inserted in the thylakoid membrane. FIP expression was down-regulated in plants exposed to high light intensity, oxidative, salt, and osmotic stresses, whereas mutant plants expressing low levels of FIP were more tolerant to these abiotic stresses. Our data shows a new thylakoid-membrane protein involved with abiotic stress response in Arabidopsis thaliana.